Nuclear medicine technology : review questions for the board examinations - Mantel, Eleanor; Reddin, Janet S.; Cheng, Gang; Alavi, Abass (Cham : Springer, 2018)
This book prepares students and technologists for registry examinations in nuclear medicine technology by providing practice questions and answers with detailed explanations, as well as a mock registry exam. The questions are designed to test both the basic knowledge required of nuclear medicine technologists and the practical application of that knowledge. The topics covered closely follow the content specifications and the components of preparedness as published by the certification boards. This 5th edition includes expanded coverage of positron emission tomography, multimodality imaging, and other new procedures and practices in the field of nuclear medicine and molecular imaging.
Introduction -- Radioactivity, Radiopharmacy and Quality Assurance -- Radiation Safety -- Instrumentation and Quality Assurance -- Image Presentation and Computers -- Skeletal System Scintigraphy -- Central Nervous System Scintigraphy -- Cardiovascular System Scintigraphy -- Respiratory System Scintigraphy -- Gastrointestinal Tract Scintigraphy -- Genitourinary System Scintigraphy -- Gncologic Scintigraphy -- Infection Scintigraphy -- Endocrine System Scintigraphy -- Non-Imaging Procedures and Radionuclide Therapy -- Patient Care -- Basic PET Principles -- Multi-Modality Imaging. Appendix 1: Mock Examination -- Appendix 2: Answers to Chapter 2 -- Appendix 3: Answers to Chapter 3 -- Appendix 4: Answers to Chapter 4 -- Appendix 5: Answers to Chapter 5 -- Appendix 6: Answers to Chapter 6 -- Appendix 7: Answers to Chapter 7 -- Appendix 8: Answers to Chapter 8 -- Appendix 9: Answers to Chapter 9 -- Appendix 10: Answers to Chapter 10.- Appendix 11: Answers to Chapter 11.- Appendix 12: Answers to Chapter 12.- Appendix 13: Answers to Chapter 13.- Appendix 14: Answers to Chapter 14.- Appendix 15: Answers to Chapter 15.- Appendix 16: Answers to Chapter 16 -- Appendix 17: Answers to Chapter 17.- Appendix 18: Answers to Chapter 18.- Appendix 19: Mock Examination Answers.
Master record variable field(s) change: 050, 650 - OCLC control number change
Keywords: Nuclear medicine -- Examinations -- Study guides; Medical technologists -- Licenses -- United States -- Study guides; Radiologic technologists -- Examinations -- Study guides; Nuclear Medicine; Electronic books; Study Guide; Examination Questions